KEBENARAN ILMIAH DALAM PERSPEKTIF FILSAFAT ILMU - Rumah jurnal, Dilaulia Azrah (Cemara Education and Science, 2025)
Humans struggle in their lives to seek and find essential truth gives rise to several fundamental questions, namely does wonder really exist? And if so, what is truth? How do humans obtain it? What is the nature of truth itself, namely is it relative or absolute? And these questions will continue to develop in accordance with the problems faced by humans themselves. It began in Ancient Greece, namely one of its figures, Socrates, although indirectly, who had laid the foundations of scientific truth with his assumption that there is objective truth, there is good behavior and there is bad behavior. Then there are appropriate actions and there are bad actions. Then continued by his student Plato who said that truth as an unhidden existence cannot be achieved by humans while in this world. In other wor